Arahan Pengembangan Desa sebagai Pusat Pertumbuhan dalam Mendukung Kawasan Agropolitan di Kabupaten Barru - Muhammad Irsam S. Ali; Abdul Rachman Rasyid; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
South Sulawesi Province Regional Spatial Plan 2009-2029 establishes Barru Regency as one of the strategic areas in the agropolitan area, while the 2011-2031 Barru Regional Spatial Plan establishes a strategic area in the agropolitan area in Barru and Pujananting Districts, in implementing the agropolitan concept first determine the growth center village then carried out an assessment based on Practical Guidelines for Identifying the Location of Selected Areas Village Development Centers by the Directorate of Settlement Development, Directorate General of Ciptakarya, Ministry of Public Works (2006) then the results of the assessment are used as a reference in determining direction for developing growth center villages with the highest score. The results of this study indicate that there is no village included in the classification of growth center villages only included in the classification of potential village growth center villages so that the selected village is the village with the highest score, In Barru Subdistrict the highest score is Tompo Village while Pujananting Village is Bulo Village -Bulo. Direction to develop Tompo Village Barru District and Bulo-Bulo Village Pujananting District in order to be classified as a growth center village, the aspects that need to be developed are village classification, clean water facilities, lighting facilities, dominant number of houses, management of agricultural activities, number of factories, potential economic sectors, market facilities, credit facilities, environmental sanitation facilities (waste), health facilities, recreational facilities, and transportation facilities.